Not Whether But When : The U.S. Decision to Enlarge NATO - Goldgeier, James M. (Book collections on Project MUSE., 2010)
How did Poland, Hungary, and the Czech Republic become the newest members of the North Atlantic Treaty Organization? Based on interviews conducted with more than 75 individuals#x97;from Cabinet officials to desk officers#x97;James M. Goldgeier tells the inside story of this controversial Clinton administration initiative. Analyzing the earliest internal deliberations, as well as administration discussions with allies, the Russians, and the United States Senate, Goldgeier demonstrates how a handful of committed policymakers outmaneuvered overwhelming bureaucratic opposition. He shows the role of domest.